Film Animasi Malaysia: Narasi Verbal ke Visual - Ahmad Nizam bin Othman (Journal of Visual Art and Design, 2009)
Among the issues are to look into the approaches and education problems that happen in the verbal narration in old society and how the construction and preservation of legends and folklore into animation forms. This paper is to identify the icon, structure and method that use in film animation to emphasize the culture understanding of the legends and folklore. The ideas of this paper are to identify form; icon and meaning that attach in local folklore and translated into animation based on culture theory. This case study research involves collecting data through documentation; including interview method, observation and visual understanding on animation collection. The data analysis concentrates on technique and overall animation process, focusing on its impact on culture and local society. Legend and folklore are a part of Malays tradition culture that has been spreading and handing on from one generation to another. The story of fairy tales, myths, extraordinary and miraculous of early centuries of human evolution now been represent in new form, that involved visual and other human sense's. This paper will discuss about the condition of the understanding and imaginations in this new generation are still same as early century about the beauty of Mahsuri, the extraordinary and enthusiastic of Hang Tuah and the kindheartedness of Bawang Putih. How human accepted and preserves tradition and culture customs but in adaptation process, upgrading and decent with civilization maturity. The outcome are expected to contribute in preserving culture and tradition.